A COVID-19 Crisis in Child Physical Fitness: Creating a Barometric Tool of Public Health Engagement for the Republic of Slovenia - Jurak, Gregor; Morrison, Shawnda A.; Kovač, Marjeta; Leskošek, Bojan; Sember, Vedrana; Strel, Janko; Starc, Gregor (Frontiers in Public Health, 2021)
The Republic of Slovenia implements the largest longitudinal database of child physical fitness in the world– SLOfit. Slovenia has some of the most physically active children globally, and it has responded rapidly to incorporate national physical activity (PA) interventions throughout the COVID-19 pandemic. Despite aggressive campaigns to maintain PA at home, the country has seen a tremendous decrease in child physical fitness over the past several months as self-isolation measures have been mandated by national authorities. These trends prompted researchers to create a method of tracking and communicating government decisions which have a direct impact on child physical activity, fitness and overall health (i.e. the SLOfit Barometer). The research team assembled experts for consultation on creation of the SLOfit Barometer after processing preliminary data on 20,000 schoolchildren which found the greatest decline in child physical fitness since systematic testing began more than 30 years ago. Only two months of self-isolation erased over 10 years of hard-fought health gains acquired from national public health policies and PA interventions. This crisis in child fitness requires integrated community participation and a robust public health policy response, and with the SLOfit Barometer acting as a national bellwether system, it is envisioned that policy makers and the public will advocate for bold, progressive actions to combat this national health emergency. This surveillance tool tracks government action to combat the increasing child physical inactivity and obesity trends brought on as a direct result of COVID-19 isolation regulations.